WORKSHOP ONLINE PEMBELAJARAN BAHASA INGGRIS: STRATEGI BELAJAR GRAMMAR DAN STRUCTURE BAGI EFL - Bambang, Muhammad; Ariya Agustin (Lembaga Pengembangan Kinerja Dosen, 2022)
The COVID-19 pandemic has had an impact on various aspects of life. One of them is in the education aspect, the government establishes a School From Home (SFH) policy or school from home so that learning activities are carried out using online media. In addition to learning activities, training activities in the form of workshops also do not escape the online atmosphere. This activity was held to increase the enthusiasm for learning English during the pandemic, using the Zoom media which is devoted to daily activities. This training was attended by high school/vocational high school students in Palembang City and students from severaluniversities in South Sumatra Province. This activity succeeded in making the activity participants able to convey daily activities in English properly and correctly, then in this activity, the participants gained a depth of knowledge on how to use good grammar in learning English.